2018
DOI: 10.3390/rs10030384
|View full text |Cite
|
Sign up to set email alerts
|

Paddy Field Expansion and Aggregation Since the Mid-1950s in a Cold Region and Its Possible Causes

Abstract: Over the last six decades, paddy fields on the Sanjiang Plain have experienced rapid expansion and aggregation. In our study, land use and land cover changes related to paddy fields were studied based on information acquired from topographic maps and remote-sensing images. Paddy field expansion and aggregation were investigated through landscape indices and trajectory codes. Trajectory analyses showed that the transformations from marsh as well as from grassland to dry farmland and then into paddy fields were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 57 publications
2
29
0
2
Order By: Relevance
“…The natural ecological environment, which was mainly composed of the original forest, grassland, and swamp, was transformed into an artificial ecological environment dominated by farmland, leading to severe land degradation and ecological environment deterioration [44][45][46][47][48]. However, since 2005, a large amount of rain-fed farmland has been converted to paddy fields to pursue higher economic benefits [49]. As a result, the crop type for the conversion areas has changed from corn to rice, which provides a good case for studying the climate effects caused by land use management.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…The natural ecological environment, which was mainly composed of the original forest, grassland, and swamp, was transformed into an artificial ecological environment dominated by farmland, leading to severe land degradation and ecological environment deterioration [44][45][46][47][48]. However, since 2005, a large amount of rain-fed farmland has been converted to paddy fields to pursue higher economic benefits [49]. As a result, the crop type for the conversion areas has changed from corn to rice, which provides a good case for studying the climate effects caused by land use management.…”
Section: Study Areamentioning
confidence: 99%
“…Based on our previous studies, we developed the land use maps in 2005 and 2015 with humancomputer interaction interpretation based on the Landsat 5 Thematic Mapper (TM) images in 2005 and Landsat 8 Operational Land Imager (OLI) images in 2015 (https://glovis.usgs.gov/) [43,49]. Only images in May and June were used in the classification to distinguish the paddy fields from rain-fed farmland.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Different from dry farmland, paddy fields are also important artificial wetlands. Inundated in the growing season, paddy fields are important sources of methane caused by human activities [39,40], influencing the emissions of greenhouse gases (GHG). Paddy rice consumes a lot of water resources, which affects water security.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Song et al described agricultural expansion pattern in the Sanjiang Plain and indicated that the total area of agricultural continues to grow [48]. Yan et al illustrate the paddy expansion process since 1976 by combing remote-sensing images [40]. However, the detailed agricultural expansion pattern is still needed to study, such as the transformation between dry farmland and other land-use types.…”
Section: Introductionmentioning
confidence: 99%